Manifestasi Jati Diri Masyarakat Desa Latonliwo, Kecamatan Tanjung Bunga, Kabupaten Flores Timur dalam Syair Upacara Adat Tuno Li - Bernadus E. Besi Koten; Imelda Oliva Wissang; Pilipus Wai Lawet (Institut Agama Islam Sunan Giri Ponorogo, 2023)
This study aims to describe the manifestation of the identity of the people of Latonliwo village, Tanjung Bunga sub-district, East Flores district in the poetry of the Tuno Li traditional ceremony. The Tuno Li traditional ceremony is a traditional ceremony of healing sick people to save the community or an individual from an illness that cannot be cured by medical personnel. The cause of the disease comes from personal mistakes such as mistakes in speech, actions or actions that are done intentionally or unintentionally Morit No'on Koda, Koda No'on Nalan. The research method uses qualitative research. The data were in the form of verbal expressions of traditional Tuno Li ceremony poems obtained from traditional leaders as resource persons. The data collection techniques used in this study were observation, interviews and documentation. Checking the validity of the data using triangulation techniques. The results of this study are: (1) The figurative meaning in the poetry of the Tuno Li traditional ceremony, namely a) The figurative meaning of spirituality. b) The figurative meaning of social status. c) The meaning of social figures of speech. d) The figurative meaning of healing or restoration. e) The figurative meaning of giving a blessing. (2) The manifestation of the identity of the Latonliwo Village community in the Tuno Li traditional ceremony, namely a) Religious. b) Hierarchical. c) Please help. d) Compassion. e) Love.